Seasonal patterns of benthic arthropods in a subtropical Andean basin - Mesa, Leticia Mariana (2009)
We studied the seasonal variation of arthropod assemblages and the response to high discharge events in a subtropical Andean basin. Using abundance of common taxa and taxon richness of each sampled site, we examined the temporal variation of arthropods and related these changes with 12 environmental variables. Seasonal patterns of benthic arthropods were confirmed by uni- and multivariate techniques. Benthic abundance and taxon richness peaked on autumn-winter months, and declined abruptly on the month of peak discharge (summer season). Distinct taxonomic groups were dominant in each season influenced by discharge and seven chemical variables. Assemblage resistance to disturbance by spates was low. Rapid recovery of benthic arthropods after floods reflected high resilience of the system. The dominance of groups of short life cycles such as Ephemeroptera played an important role in this process.